HUBUNGAN ANTARA AKTIVITAS MENCETAK STENSIL DENGAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI - Ai Patonah (STPI Bina Insan Mulia Yogyakarta, 2025)
Stencil printing activity is one of the learning methods that is often done. During this stencil printing learning, most children look very enthusiastic. The research was conducted with the aim of examining: (1) The implementation of stencil printing activities in Group B of RA Annur Sanding Malangbong Garut; (2) The level of fine motor skills of early childhood in the group; and (3) The relationship between the two variables. The study used a correlational approach by collecting data through observation, performance, interviews and documentation. Based on data analysis, the stencil printing activity achieved an average score of 78, including in the good category in the range of 70-79. Meanwhile, children's fine motor skills received an average score of 73, also classified as good in the same interval. Product moment correlation analysis resulted in a coefficient of 0.64, indicating a strong relationship (interval 0.600-0.799). Hypothesis testing resulted in t_count = 2.623 which exceeds t_table = 2.228 at 5% significance with db = 10, indicating Ho rejection and Ha acceptance. This proves a positive and significant relationship between the two variables. The calculation of the coefficient of determination of 40.96% indicates that there are still 59.04% other factors that influence the fine motor skills of early childhood in the group.